2021
DOI: 10.1088/1755-1315/655/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera as natural coagulant in water treatment and production of antifungal soap

Abstract: The use of Moringa oleifera seed in water purification has reduced the use of chemical-based coagulants which is detrimental to both human and livestock. This project aimed at testing the microbial properties of M. oleifera seed oil extract on some selected pathogens (Bacterial and fungi). The oil was extracted using Soxhlet apparatus with ethanol as solvents. Gas-chromatography-mass spectrometry (GCMS) analyses were carried out for the identification of active components in the oil extract. The zone of inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Household wastes and Agricultural (biomass) can be very useful if properly recycled [1][2][3][4][5]. The increase in agricultural waste has endangered the lives of man and livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Household wastes and Agricultural (biomass) can be very useful if properly recycled [1][2][3][4][5]. The increase in agricultural waste has endangered the lives of man and livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical coagulants are commercially used in treatment plants but it leads health issues to the humans like Alzheimer's disease. Natural coagulants and flocculants are being replaced for chemical agents due to its extensive characters and source of origin (plants, animals, microbes and biowastes) (Ahmad et al, 2021;Ojewumi et al, 2021;Thirugnanasambandham and Karri, 2021). Anju et al (2017) and Kumar et al (2018) reported that polyglutamic acid (PGA) is a water-soluble and biodegradable anionic homopolyamide made up of L and D glutamic acid units with peptide bonds from peptide transformation, chemical synthesis, microbial fermentation and biotransformation.…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera-based natural coagulantSeveral studies have demonstrated that Moringa oleifera (MO) benefits water and wastewater treatment(Blockx et al 2018;Chua et al 2019;Moniem et al 2021;Islam et al 2022). The MO is used for hardness, turbidity, and heavy metal removal(Elemile et al 2021;Ojewumi et al 2021). Compared to a chemical-based coagulant, MO is readily available, cost-effective, eco-friendly, biodegradable, has no harmful byproducts, and produces low sludge volume(Singh & Patidar 2020;Ogunmodede et al 2021;Alazaiza et al 2022).…”
mentioning
confidence: 99%